Artrópodes em ninhos de Columba livia Gmelin, 1789 (Aves, Columbidae) em área urbana de Manaus, Amazonas, Brasil. - Ogawa, Guilherme Maerschner (EntomoBrasilis, 2008)
Foi realizado um estudo sobre artrópodes que vivem em ninhos de Columba livia Gmelin 1789, ave conhecida como pombo urbano e que nidifica em construções humanas, com o intuito de inventariar as espécies de artrópodes associadas. Foram coletados 14 ninhos de C. livia em nove bairros da área urbana de Manaus os quais foram levados ao laboratótio e colocados em um extrator do tipo Berlese-Tulgren por 12 dias, para a captura dos artrópodes. Foram encontrados 10.323 artrópodes, pertencentes a 3 subfilos, 3 classes, 14 ordens e 33 famílias. Acari foi mais abundante com 7.879 indivíduos, sendo o gênero Caloglyphus Berlese, 1923, o mais representativo (75%). A maioria das espécies encontradas é detritívora. A diversidade de artrópodes foi menor em Manaus se comparada à registrada em trabalhos da região Paleártica, provavelmente por C. livia ser uma espécie exótica na fauna Neotropical. Arthropods in the nests of Columba livia Gmelin 1789 (Aves, Columbidae) in the urban area of Manaus, Amazonas, Brazil. Abstract. The objective of this study was identify the arthropod fauna in nests of the urban pigeon, Columba livia Gmelin 1789 who build their nests in man-made buildings. Fourteen nests were collected in nine districts of the built up area of the city of Manaus. For twelve days, arthropods were extracted in a Berlese-Tulgren funnel. A total of 10.323 arthropods representing 3 subphyla, 3 classes, 14 orders and 33 families were detected. Acari was the most abundant group with 7879 individuals. Mites of the genus Caloglyphus Berlese, 1923, made up over 75 % of all arthropods collected. Most of the arthropods extracted are detrivorous and apterous. The diversity found in Manaus was lower than that reported for samples collected in the Palearctic Region, probably because C. livia is exotic in the Neotropical fauna. The introduction of this pigeon can be responsible for a major contact between some arthropods and humans.